2018
DOI: 10.1111/vde.12526
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sarolaner against generalized demodicosis in dogs in European countries: a non‐inferiority study

Abstract: Monthly oral administration of sarolaner was safe and highly effective in the treatment of generalized demodicosis in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 15 publications
2
31
0
3
Order By: Relevance
“…There were no treatment‐related adverse events observed. A subsequent noninferiority study compared the same two products in 81 client‐owned dogs . Parasitological cure in dogs treated with sarolaner was achieved in 93% after three months and 100% after five months, confirming the efficacy of sarolaner against canine generalized demodicosis.…”
Section: Treatmentmentioning
confidence: 84%
“…There were no treatment‐related adverse events observed. A subsequent noninferiority study compared the same two products in 81 client‐owned dogs . Parasitological cure in dogs treated with sarolaner was achieved in 93% after three months and 100% after five months, confirming the efficacy of sarolaner against canine generalized demodicosis.…”
Section: Treatmentmentioning
confidence: 84%
“…Across Albania (60), Germany (3), Spain (7), Portugal (14), and Poland (50), 134 dogs were enrolled, ranging in age in the oral uralaner group from 10 weeks to 13 years (mean 3.1; standard deviation ± 2.9 years), in the spoton uralaner group from 4 months to 12 years (3.5 ± 3.2 years), and in the topical imidacloprid-moxidectin group from 11 weeks to 9 years (2.9 ± 2.9 years). A broad range of breed categories was represented, with approximately 50% of dogs mixed breed, 22% were companion-toy dogs, and approximately 9% were terriers.…”
Section: Resultsmentioning
confidence: 99%
“…Where necessary (e.g. long or medium-haired dogs), hair was removed at the area to be scraped, and the skin was rmly squeezed prior to and during scraping to eject mites from hair follicles [2,14,15]. Scrapings were made in the direction of hair growth with a blade or spatula, covered with mineral oil, until capillary oozing was observed.…”
Section: Assessments Of Demodicosismentioning
confidence: 99%
See 1 more Smart Citation
“…All five studies were sponsored by the pharmaceutical companies that make the isoxazoline preparations and nearly all authors were employees of these companies. This may bias study design and reporting of results as demonstrated in the study by Becskei et al (2018) where sarolaner is claimed to be as good as, if not better than moxidectin/imidacloprid, but the study was only designed to prove non-inferiority. In each paper the dosing frequency of moxidectin/imidacloprid varied making them harder to compare.…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%